COMPARISON BETWEEN ECHOCARDIOGRAPHY AND CARDIAC COMPUTED TOMOGRAPHY FOR THE DIAGNOSIS OF CONGENITAL HEART DISEASES - KALSOOM , F; ZAFAR , U; MUSHTAQ , K; TARIQ , S (Biological and Clinical Sciences Research Journal, 2023)
Congenital heart disease (CHD) is a significant cause of morbidity and mortality worldwide. Accurate diagnosis is crucial for appropriate management and intervention. Echocardiography and cardiac computed tomography (CT) are commonly used for diagnosing CHD, yet their diagnostic reliability in a specific clinical setting requires evaluation. The objective of the study was to assess the diagnostic reliability of echocardiography and cardiac computed tomography (CT) for congenital heart disease (CHD) at Jinnah Hospital in Lahore. A cross-sectional study was conducted at the Department of Radiology, Chaudhary Pervez Ellahi Institute of Cardiology, from January 2022 to December 2022. One hundred patients suspected of congenital cardiac disorders were enrolled, spanning various age groups. Data were collected retrospectively, including procedure notes, CT scan results, echocardiograms, and demographic information. Descriptive statistics were used to analyse the data, with median and percentiles calculated using SPSS. A significance level of p < 0.05 was considered statistically significant. Of the 100 patients included in the study, 69 were men, and 31 were women, with ages ranging from a few days to eighteen years. Two categories of malformations were identified: intracardiac and extracardiac. Using surgical and conventional angiography results as the gold standard, 544 anomalies were confirmed and analysed, including 46 extracardiac and 196 intracardiac findings. Echocardiography demonstrated an overall diagnostic accuracy of 96.86%, while cardiac CT exhibited a diagnostic accuracy of 98.27% for cardiac congenital abnormalities. Based on the results, the cardiac computed tomography (CT) provides superior visualization of extracardiac abnormalities, with a diagnostic accuracy of 99.02%. In contrast, echocardiography remains the preferred modality for detecting intracardiac anomalies, boasting a diagnostic accuracy of 99.31%. The complementary use of echocardiography and cardiac CT enhances the assessment and evaluation of congenital heart diseases, facilitating surgical planning and intervention.